2013
DOI: 10.3109/15569527.2013.835817
|View full text |Cite
|
Sign up to set email alerts
|

Acute serous macular detachment and cystoid macular edema after uncomplicated phacoemulsification using standard dose subconjunctival cefuroxime

Abstract: Acute toxic serous macular detachment after cataract surgery is very rare, and has been described previously with the use of high concentrations of intra-cameral cefuroxime. We report a case of serous macular detachment and cystoid macular edema 1 day after uncomplicated phacoemulsification using standard dose subconjunctival cefuroxime at the end of surgery. Our case demonstrates that subconjunctival cefuroxime may cause retinal toxicity in a similar fashion to intra-cameral cefuroxime, possibly due to entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 7 publications
1
14
1
4
Order By: Relevance
“…In a recent case series, early transient macular edema was attributed to dilution error of intracameral cefuroxime (9 mg/0.1 mL) injected during a single day phacoemulsification. 1 There are some other reported cases in which 2 mg/ 0.1 mL 2 or even a standard dose (1 mg/0.1 mL) of intracameral 3 or subconjuntival cefuroxime 4 was associated with transient macular edema.…”
Section: Transient Macular Edema After Standard Dose Of Intracameral mentioning
confidence: 99%
“…In a recent case series, early transient macular edema was attributed to dilution error of intracameral cefuroxime (9 mg/0.1 mL) injected during a single day phacoemulsification. 1 There are some other reported cases in which 2 mg/ 0.1 mL 2 or even a standard dose (1 mg/0.1 mL) of intracameral 3 or subconjuntival cefuroxime 4 was associated with transient macular edema.…”
Section: Transient Macular Edema After Standard Dose Of Intracameral mentioning
confidence: 99%
“…[2829] However, a prospective study found that ICC at the standard dose of 1 mg/0.1 mL did not have a statistically significant effect on postoperative macular thickness compared with nonadministration of intracameral antibiotic;[30] although, this study was under-powered to detect rare events. The ESCRS study and other longitudinal cohort studies were not designed to assess safety or adverse events as primary endpoints, but a large number of patients enrolled without a reported increase in these adverse events suggests that they are not associated, are masked by confounding factors, or are exceedingly rare.…”
Section: Resultsmentioning
confidence: 99%
“…Intracameral cefuroxime caused retinal hemorrhage and infarction that resulted in very poor visual acuity in four patients in one published series,3 because of an inadvertent overdose of drug administered after uneventful cataract surgery. Two papers reported retinal toxicity from the use of a standard dose of cefuroxime, administered intracameral or subconjunctival, after uncomplicated cataract surgery 4,5. The authors described an acute macular detachment with intraretinal fluid which appeared at day 1–2 postoperatively and disappeared spontaneously at day 6–7.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these exciting results, intracameral cefuroxime is not used everywhere in Europe and in US, mostly because of some concerns about costs and dilution errors that could lead to severe retinal complications, such as hemorrhagic retinal infarction 3. One case of acute toxic serous macular detachment with cystoid macular edema was reported using intracameral cefuroxime and one after subconjunctival cefuroxime at correct concentration 4,5. Vitreoretinal surgery, as well, could lead to POE, and to our knowledge there are no reports about the use of intracameral cefuroxime in vitreoretinal surgery.…”
Section: Introductionmentioning
confidence: 99%